PENDIDIKAN AGAMA KATOLIK SEBAGAI MEDIA KOMUNIKASI IMAN BAGI REMAJA DI STASI SANTO FRANSISKUS BENANGIN - Nurbeta Nurbeta; Silvester Adinuhgra; Fransiskus Janu Hamu; Widya Ariyani (Sekolah Tinggi Pastoral Tahasak Danum Pambelum Keuskupan Palangkaraya, 2019)
The purpose of this thesis is to depart from the problems faced by Catholic adolescents, relating to the number of teenagers not active in activities in the Church, and falling into promiscuity. Departing from this issue, the need for the role of Catholic Religious Education to transfer the values of Faith to Catholic youth. Thesis entitled